Extrato hidroalcóolico de Euterpe oleracea MART. (açaí) modula a mucosite intestinal induzida por 5-Fluorouracil em camundongos por meio da sinalização TIR-4/MyD88/PI3Ka/mTORr/NF-kBp65 - Fiorio, Bárbara de Cerqueira (2020)
5-fluorouracil (5-FU) is an antineoplastic agent effective in the treatment of solid tumors. However, it has important side effects that limit treatment, including intestinal mucositis. Euterpe oleracea Mart. is a plant from the Amazon region popularly known as açaí that has high antioxidant and anti-inflammatory activity attributed to the phenolic compounds present in the fruit. This study aimed to evaluate histopathological and functional changes, oxidative stress and inflammation in mice with intestinal mucosa lesions induced by 5-FU and the effects of treatment with hydroalcoholic açaí stone extract (ASE) on these parameters. Swiss mice, weighing 25-30g, were separated into five large groups: one received a single intraperitoneal injection of 5-FU (450 mg / kg, ip), another received saline (5 mL / kg, orally) and the others were separated into three groups that received an ASE treatment, 30 min. before mucositis induction with 5-FU, at doses of 10, 30 or 100 mg / kg, orally; this treatment remained for the next 3 days, up to 30 min. before euthanasia. Weight loss of the animals was evaluated for 3 days. On day 3 after 5-FU treatment, the animals were euthanized and intestinal samples were collected and evaluated for histopathological scores; levels of glutathione (GSH), malondialdehyde (MDA), nitric oxide (NO) and myeloperoxidase (MPO); level of TNF-α and IL-1β cytokines; gastric emptying; intestinal barrier integrity; gene expression of TLR-4, MyD88, PI3Ka, mTOR and NF-κBp65 and protein expression of TLR-4 and NF-κBp65. 5-FU induced weight loss in animals, intestinal lesions, significant impairment of epithelial barrier function, shortening of intestinal villi, cell vacuolization, infiltration of polymorphonuclear cells, loss of epithelial cells, free radical production (NO), GSH depletion, increased MDA, increased levels of IL-1β and TNF-α, delayed gastric emptying, increased expression of the TLR-4, MyD88, PI3Ka, mTOR and NF-κBp65 genes, increased expression of TLR-4 and NF- κB. ASE (100 mg / kg) significantly reduced the animals' weight loss, reversed intestinal lesions, recovered villus height, decreased neutrophil infiltration and MPO levels, decreased nitrate and MDA levels, increased glutathione concentration, reduced levels of IL-1β and TNF-α, restored the integrity of the intestinal barrier, reduced the expression of the TLR-4, MyD88, PI3Ka, mTOR and NF-κBp65 genes and the expression of the TLR-4 and NF-κB proteins. We concluded that ASE reduced inflammation and oxidative stress, reversed histological changes and attenuated functional changes by reducing the gene expression of the TLR- 4/MyD88/PI3Ka/mTOR/NF-κBp65 pathway.